Online Involvement for Georgia Student Teachers During Covid-19 - Thomas, Michelle A.; Norgaard, Martin; Stambaugh, Laura A.; Atkins, Rebecca L.; Kumar, Anita B.; Farley, Alison L. P. (Frontiers in Psychology, 2021)
As concerns about COVID-19 rapidly escalated in March 2020 in the United States, all levels of education were impacted. Student Teachers, or pre-service teachers (PST), are university students finishing a degree and/or teacher certification program by serving as an intern in a school setting. The purpose of this study was to examine how the sudden shift away from traditional face-to-face instruction co-teaching, and mentorship affected the involvement of music PSTs and their CT mentors in one region of the United States. Specifically, the research questions were: 1) How and in what ways were PSTs involved in planning, instruction, and/or assessment synchronously and asynchronously after school closures? 2) In what subdomains (performance, music theory/ear-training, etc.) were PSTs engaged in instruction and learning activities? 3) What challenges and solutions did PSTs report related to Covid-19 closures? A survey was sent, to PSTs attending teacher preparation programs at universities in the state of Georgia at the end of the spring semester. Thirty-seven participants responded to the survey questions representing about 32% of all PSTs in Georgia in Spring 2020. Twenty-one were not given access to the online teaching platform of their placement school. A thematic analysis of the open-ended questions identified common themes including whether experiences were perceived as negative or positive. Of the PSTs given access, the majority of their responsibilities and experiences were creating assignments, additional help videos, participating in Zoom meetings, and assessing student assignment submissions. Of these experiences, most were classified as positive by the PSTs. However, the importance of face-to-face interactions for both PST and the P-12 students was mentioned throughout survey responses. Ten PSTs mentioned their CT relationship/ interaction and 4 of the respondents noted that their CT never reached out for help, however 6 noted collaborative meetings or teaching with their CT. Importantly, some PSTs reported a lack of knowledge related to the planning and implementation of music instruction in the online modality. Therefore, teacher preparation programs should consider incorporating technology including online solutions into the music curriculum so that future music educators may more flexibly incorporate both in-person and distance learning.